MANAGERIAL ACCOUNTING, PLANNING, CALCULATION AND ANALYSIS OF COST OF PRODUCTION IN THE CONDITIONS OF MARKET ECONOMY (METHODOLOGICAL ASPECT) - Shulha, O. V.; Lohvynenko, O. V. (Science and Transport Progress, 2007)
Problems of function of the system of planning and analysis of prime cost of output simultaneously with reformations of the system of accounting in accordance with national standards of accounting are considered.